FEATURES OF TEACHING COMPUTER SCIENCE IN AN INCLUSIVE EDUCATION ENVIRONMENT - Baiganova, А.М.; Narymbaeva, М.А. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
With the development of inclusive education, the adaptation of teaching methods for computer science to meet the needs of children with special educational requirements is becoming increasingly important. This article explores the specific features of teaching computer science in an inclusive environment, with a focus on the development and implementation of digital educational resources and teaching methods that address the needs of children with disabilities. As part of the study, an experiment is being conducted on the implementation of an educational booklet on basic computer literacy for children with intellectual disabilities (ID). To assess its effectiveness, a combination of pedagogical and psychological diagnostic methods is used, including testing, surveys, observation, and psychological techniques such as the "Success Ladder," correctional test, incomplete sentences method, and projective techniques. Furthermore, the article examines the potential of modern technologies such as artificial intelligence, multimedia resources, and adaptive learning systems to personalize the educational process. The study provides practical recommendations for the development of inclusive digital educational platforms and instructional materials aimed at improving the accessibility and effectiveness of computer science education for all learners. The results of this research may be beneficial for educators, educational technology developers, and specialists in inclusive education working to enhance the quality of computer science instruction in diverse learning environments.